2019
DOI: 10.1007/s00394-019-02143-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes of trace element status during aging: results of the EPIC-Potsdam cohort study

Abstract: Purpose We aimed to evaluate age-dependent changes of six trace elements (TE) [manganese (Mn), iron (Fe), zinc (Zn), copper (Cu), iodine (I), and selenium (Se)] over a 20-year period. Methods TE concentrations were determined using repeated serum samples taken at baseline and after 20 years of follow-up from 219 healthy participants of the EPIC-Potsdam study, using inductively coupled plasma tandem mass spectrometry. For each TE, absolute and relative differences were calculated between the two time points, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 47 publications
8
38
1
Order By: Relevance
“…However, in vivo the effects were rather small under conditions of a mild modulation of the Cu status in the adequate to suboptimal concentration range in healthy, young mice. The average human serum concentration of Cu ranges from 15 to 31.5 μM [ [75] , [76] , [77] ], and thus concentrations used in cell culture experiments are adequate to supplemented. But under pathophysiological conditions up to 200 μM Cu were reported in serum [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo the effects were rather small under conditions of a mild modulation of the Cu status in the adequate to suboptimal concentration range in healthy, young mice. The average human serum concentration of Cu ranges from 15 to 31.5 μM [ [75] , [76] , [77] ], and thus concentrations used in cell culture experiments are adequate to supplemented. But under pathophysiological conditions up to 200 μM Cu were reported in serum [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also under physiological conditions, serum Cu concentrations can be increased as recently described when comparing a subcohort of the EPIC Potsdam cohort which has been reinvited after 20 years. Advanced age was associated with increased Cu concentrations and decreased Se concentrations [ 76 ]. This indicates that an age-related decline in selenoprotein expression most probably is a result of a combination of lower Se concentrations and higher Cu concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of Nrf2 levels and responsiveness is a relevant health condition that physiologically takes place during aging [38]. Thus, the question arises whether age-specific changes in TE profiles [39] might be related to Nrf2. Recently, it has been examined that Nrf2 activity levels strongly differ in the liver of male and female mice [40].…”
Section: Discussionmentioning
confidence: 99%
“…Both Se deficiency and excess levels have been shown to influence the redox status and lead to severe adverse health consequences in animals and humans [10,21]. Interestingly, recently it has been demonstrated that plasma Se concentrations tend to decline in certain healthy human populations comprised of older subjects [22]. It was also reported that Se bioavailability was impacted by aging [13,23].…”
Section: Introductionmentioning
confidence: 99%